Antibacterial Activity of Ethanol Extract of Nettle Leaves against Cutibacterium acnes and Pseudomonas aeruginosa - Zuhairiah Nasution; Fira Yunita; Murniaty Simorangkir; Saronom Silaban; Nora Susanti (Indonesian Journal of Chemical Science and Technology (IJCST), 2026)
Acne vulgaris is a common skin disorder associated with the growth of Cutibacterium acnes and Pseudomonas aeruginosa. This study aimed to evaluate the antibacterial activity of ethanol extract of nettle leaves (Urtica dioica) against both bacteria. The extract was obtained by maceration using 96% ethanol and subjected to phytochemical screening. Antibacterial activity was tested using the disc diffusion method at concentrations of 200, 400, and 800 mg/mL. The findings demonstrated that the extract contained alkaloids, phenolics, flavonoids, steroids, and saponins. The inhibition zones against Cutibacterium acnes were 14.17±0.21 mm, 16.03±0.76 mm, and 17.37±1.33 mm, while against Pseudomonas aeruginosa they were 9.63±0.51 mm, 12.23±0.40 mm, and 14.33±0.47 mm, respectively. Statistical analysis showed significant differences among treatments (p<0.05). These findings indicated that Urtica dioica leaf extract may serve as a potential natural antibacterial agent against acne-associated bacteria.